Lipid Alterations in Chronic Nonspecific Low Back Pain in the Chinese Population: A Metabolomic and Lipidomic Study - Wen Tang; Hong-Jiang Wang; Su-Ying Luo; Si-Yun Zhang; Hao Xie; Hua-Qing Chen; Chu-Huai Wang; Zhou Zhang (Bioengineering)
Chronic nonspecific low back pain (cNLBP) accounts for approximately 90% of low back pain cases, affecting 65–80% of the population and significantly impacting life quality and productivity. This condition also leads to substantial financial burden. Although there have been advancements, a comprehensive understanding of the underlying etiology of cNLBP remains elusive, resulting in less than optimal treatment outcomes. This study aimed to examine the correlation between lipid variations and the development of cNLBP. The cohort consisted of 26 healthy volunteers (HV group) and 30 cNLBP patients, with an assessment of metabolites and lipid composition in both groups. Metabolomic results revealed significant alterations in lipid-associated metabolites between the HV and cNLBP groups. Subsequent lipid analysis revealed that monoacylglycerols (MAGs) increased approximately 1.2-fold (p = 0.016), diacylglycerols (DAGs) increased approximately 1.4-fold (p = 0.0003), and phosphatidylserine (PS) increased approximately 1.4-fold (p = 0.011). In contrast, triacylglycerol (TAG) decreased to about 0.7-fold (p = 0.035) in the cNLBP group compared to the HV group. The contrasting trends in MAG/DAG and TAG levels indicated that the imbalance between MAG/DAG and TAG may have an impact on the development of cNLBP. This study has provided new insights into the relationship between the progression of cNLBP and specific lipids, suggesting that these lipids could serve as therapeutic targets for cNLBP.